Prognosis analysis of lobectomy and sublobar resection in patients ≥75 years old with pathological stage I invasive lung adenocarcinoma of ≤3 cm: a propensity score matching-based analysis - Chen, Chunji; Ni, Qiming; Shi, Yubo; Fu, Shijie; Pan, Xufeng; Wang, Yiyang; Yang, Jun; Wang, Rui (Translational Cancer Research; Vol 8, No 2 (April 30, 2019): Translational Cancer Research, 2019)
Background: To determine the clinical prognosis after sublobectomy versus lobectomy in elderly patients ≥75 years old with stage I invasive lung adenocarcinoma ≤3 cm in size. Methods: In patients ≥75 years old, 255 patients were diagnosed with stage I invasive lung adenocarcinoma ≤3 cm in size between 2010 and 2014 in Shanghai Chest Hospital, they were all treated with sublobectomy or lobectomy. Potential confounding factors that consisted in the baseline characteristics of these two groups was balanced by the method of propensity score matching (PSM). The stratified analysis was conducted to compare the relapse-free survival (RFS) and lung cancer special survival (LCSS) rates in the sublobectomy and lobectomy groups. Results: As for the 255 patients, 112 cases conducted sublobectomy and 143 with lobectomy. Significant difference existed in RFS before (P=0.002) and after (P=0.010) PSM. Similarly, we still recognized significant difference in LCSS between the two groups before (log-rank P